Study of Chemical Yield after γ-Irradiation Treatment on Nuclear Grade Ion Exchanger, Indion-223 - Lokhande, R.S.; R. Kolte, Arvind; S. Prabhavalkar, Tirtha (Asian Journal of Chemistry, 2010)
Radiation treatment is given to the nuclear grade polystryrene resin Indion-223 using cobalt-60 gamma rays in different salt forms. The H2SO4 yield has been estimated which was found to increase as a function of absorbed dose and it is dependent on the counter action in the resin matrix. The estimation of the effluent of the exchanger was also carried out for its BaSO4 content which also increases with the radiation dose of the exchanger.